Health-related quality of life and utility values associated to hypoglycemia in patients with type 1 diabetes mellitus treated in the Brazilian Public Health System: a multicenter study. Issue 1 (December 2017) - Bahia, Luciana; Kupfer, Rosane; Momesso, Denise; Cabral, Debora; Tschiedel, Balduino; Puñales, Marcia; Lavigne, Suzana; Façanha, Cristina; Forti, Adriana; Mendes, Angela; Tura, Bernardo
Abstract Background Hypoglycemia is a critical and limiting factor of a good metabolic control and can adversely affect the quality of life of diabetic patients. The aim of the study was to evaluate the health-related quality of life and calculate utilities values associated with hypoglycemia in patients with type 1 diabetes mellitus (T1DM). Methods A multicenter, cross-sectional and observational study with T1DM patients from reference centers of the Brazilian public health system was conducted in three cities. Demographic and clinical data were collected, besides details on the frequency and severity of hypoglycemia. Health-related quality of life was assessed using EQ-5D instrument and utility values generated. Results 221 patients (107 women, 114 men), aged 29.8 ± 11.6 and disease duration of 14.2 ± 9.1 years were included. Most patients (n = 214, 96.8%) reported at least one symptomatic hypoglycemia in the last three months, 68% (n = 150) reported nocturnal episodes and 34.8% (n = 77) reported severe episodes. High frequency (daily or weekly) was observed in 38.6 and 26% of those reporting nocturnal or severe hypoglycemia, respectively. The median visual analog scale was 70 [60–85] for all patients, with differences between those with and without severe hypoglycemia (70 [60–80] vs 80 [61–90]; p = 0.006) and those with high and low frequency (62.5 [50–72.25] vs 70 [60–80]; p = 0.007). The median utility values was 0.801 [0.756–1.000] for all patients, with difference between those with high and low frequency of severe episodes (0.737 [0.628–1.000] vs 0.801 [0.756–1.000]; p = 0.02). Conclusions This study shows the high frequency of hypoglycemia in a sample of T1DM patients treated in three reference centers of the Brazilian public health system and the impact of severe episodes on health-related quality of life. Utility values were generated and can be used in economic analysis for treatments that could decrease hypoglycemia and consequently improve quality of life.